One species does not replace a community: functional roles of co-occurring translocated and endemic mycophagous mammals - A. Naccarella; C. Truong; E. G. Ritchie; D. R. Sutherland; A. Coetsee; A. R. Rendall (Oecologia, 2026)
Biodiversity decline alters species interaction networks and can destabilise ecosystem functions. Fungal consumption by mammals supports ectomycorrhizal (ECM) spore dispersal, contributing to fungi-plant symbioses. The ecological impacts of losing mycophagous mammals and to what extent species roles are redundant or complementary remains poorly quantified. Using fungal ITS2 metabarcoding, we explore the fungal community in scats of a translocated fungal generalist, the eastern barred bandicoot ( Perameles gunnii ), on Phillip and French Island in southeast Australia. We compare: (1) fungi in bandicoot scats and soil; (2) soil fungi, soil properties and vegetation to compare possible fungal availability across habitats; and (3) fungi within the scats of two sympatric mammals, an endemic fungal generalist (swamp wallaby, Wallabia bicolor , on Phillip Island) and fungal specialist (long-nosed potoroo, Potorous tridactylus trisulcatus , on French Island). We found diverging patterns between soil fungi and mammal diet; and between soil fungi, soil properties and vegetation across sites. On French Island, bandicoot and potoroo scats had similar ECM fungal richness, although community composition differed, with less ECM observed in soils. On Phillip Island, only one scat from the wallaby contained ECM fungi, while soils were more ECM diverse than bandicoot scat. Our findings suggest the functional roles of mycophages should not be considered interchangeable across ecosystems. Translocated bandicoots may have the capacity to perform functionally unique roles compared to resident mycophages, highlighting that translocations could provide multiple ecosystem benefit. Adequately assessing functional redundancy or complementarity requires a site-specific characterisation and comparison of the cumulative roles of co-occurring mycophagous mammals.